Cross-section calculations of (n, 2n) and (n, p) reactions for 69,71Ga and 75As target nuclei up to 20 MeV - H. Sahan; M. Sahan; E. Tel (Ядерна фізика та енергетика)
In the present research, neutron induced reaction cross sections of 69,71Ga(n, 2n), 69,71Ga(n, p), 75As(n, 2n) and 75As(n, p) were investigated up to 20 MeV. Three theoretical calculation codes (EMPIRE 3.2, TALYS 1.6 and ALICE/ASH) were used for model calculations based on the Weisskopf - Ewing and Hauser - Feshbach theories. The results of theoretical calculations were compared with some empirical formulas developed by different researches, with evaluated nuclear data sets (JENDL-4.0u2 (2012), TENDL-2015, JEFF-3.2 (2014), and ENDF/B-VIII.0 (2018)) and also with the available experimental data found in literature.